Age-Associated Pathology and Functional Outcomes After Hip Arthroscopy in Female Patients: Analysis With 2-Year Follow-up. Issue 13 (November 2020) - Bloom, David A.; Fried, Jordan W.; Bi, Andrew S.; Kaplan, Daniel J.; Chintalapudi, Nainisha; Youm, Thomas
Background: Previous research has demonstrated a statistically significant relationship between hip arthroscopy outcomes and age. Purpose: To investigate the link, if any, between hip arthroscopy outcomes and intraoperative pathology as well as with patient age and sex. Study Design: Cohort study; Level of evidence, 3. Methods: Of 272 female patients aged ≥14 years undergoing primary hip arthroscopy for femoroacetabular impingement between August 2010 and September 2017, and with 2-year patient-reported outcome scores, a total of 194 (71.3%) were included for final analysis. These patients were separated into 3 age-based cohorts: <30 years (n = 44), 30 to 45 years (n = 74), and >45 years (n = 76). Their data were then analyzed and compared with respect to patient characteristic information, intraoperative pathology, and functional outcome scores for statistical significance, which was set at P < .05. Results: When an analysis of variance was conducted for the 3 age groups at 2-year follow-up, there was a statistically significant difference for modified Hip Harris Score ( P = .0003; <30 years, 88.26 ± 13.1 [mean ± SD]; 30-45 years, 82.68 ± 18.0; >45 years, 75.03 ± 19.5). The results of an analysis of variance comparing 2-year Non-arthritic Hip Score were also statistically significant ( P = .0002; <30 years, 89.9 ± 13.7; 30-45 years, 85.8 ± 15.8; >45 years, 78.1 ± 17.2). Results of logistic regression demonstrated that the odds of a cam-type lesion decreased by 0.971 for every additional year in age among female patients. The odds of achieving the patient-acceptable symptomatic state decreased by a factor of 0.96 for each additional year in age ( P < .0004). Conclusion: Surgical treatment of femoroacetabular impingement in females led to improved functional outcomes at 2 years of follow-up, although older female patients did worse after hip arthroscopy as compared with their younger counterparts. There may be an age-dependent decrease in incidence of cam-type lesions in female patients.